Effects of dynamic resistance exercise on bone mineral density in postmenopausal women: a systematic review and meta-analysis with special emphasis on exercise parameters - Shojaa, Mahdieh; von Stengel, Simon; Kohl, M.; Schöne, Daniel; Kemmler, Wolfgang (Osteoporosis international, 2020)
This systematic review and meta-analysis set out to determine the effect of dynamic resistance exercise (DRT) on areal bone mineral density (aBMD) in postmenopausal women and derive evidence-based recommendations for optimized training protocols. A systematic review of the literature according to the PRISMA statement included (a) controlled trials, (b) of isolated DRT with at least one exercise and one control group, (c) with intervention durations ≥ 6 months, (d) aBMD assessments at lumbar spine or proximal femur, (e) in cohorts of postmenopausal women. We searched eight electronic databases up to March 2019 without language restrictions. The meta-analysis was performed using a random-effects model. Standardized mean differences (SMD) for BMD changes at lumbar spine (LS), femoral neck (FN), and total hip (TH) were defined as outcome measures. Moderators of the exercise effects, i.e., “intervention length,” “type of DRT,” “training frequency,” “exercise intensity,” and “exercise volume,” were addressed by sub-group analyses. The study was registered in the international prospective register of systematic reviews (PROSPERO) under ID: CRD42018095097. Seventeen articles with 20 exercise and 18 control groups were eligible. SMD average is 0.54 (95% CI 0.22–0.87) for LS-BMD, 0.22 (0.07–0.38) for FN-BMD, and 0.48 (0.22–0.75) for TH-BMD changes (all p ≤ 0.015). While sub-group analysis for FN-BMD revealed no differences within categories of moderators, lower training frequency (< 2 sessions/week) resulted in significantly higher BMD changes at LS and TH compared to higher training frequency (≥ 2 sessions/week). Additionally, free weight training was significantly superior to DRT devices for improving TH-BMD. This work provided further evidence for significant, albeit only low–moderate, effects of DRT on LS-, FN-, and TH-BMD. Unfortunately, sub-analysis results did not allow meaningful exercise recommendations to be derived. This systematic review and meta-analysis observed a significant low–moderate effect of dynamic resistance exercise on bone mineral density changes in postmenopausal women. However, sub-group analyses focusing on exercise characteristics found no results that enable the derivation of meaningful exercise recommendations in the area of exercise and osteoporosis prevention or therapy.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Bone mineral density; Dynamic resistance exercise; Exercise characteristics; Postmenopausal women